Understanding the influence of unsteady and convection terms in heat transfer model on the predicted heat flux in engines operated under different combustion modes. (1st November 2022) - Cao, Jingjie; Jia, Ming; Li, Yaopeng; Liu, Hong
Highlights: Enhanced heat transfer models focusing on the transient and convection effects are constructed. Coupling relationships among the unsteady terms and their contributions to the heat flux are understood. CDC, HCCI and RCCI modes are all insensitive to the unsteady terms in the energy equation. Computational accuracy of heat flux is enhanced with the consideration of the convection efforts for CDC mode. Abstract: The aim of current research is to develop an enhanced heat transfer model to accurately predict the heat flux through the cylinder walls during the working process of internal combustion engines operated under different loads and combustion modes. Two enhanced models, i.e., the unsteady model and the steady convective contribution (SCC) model were respectively constructed based on the thermal wall function. The effects of the transient ambient gas temperature and pressure variations, as well as the chemical reaction source term, were included in the unsteady model. Then the contributions of the unsteady terms, such as the temporal derivative of gas temperature, the pressure work, and the chemical heat source in the energy equation were analyzed in detail. The results indicate that the mechanism of the unsteady heat transfer process is different in the engine operated under motored conditions and different combustion modes, including conventional diesel combustion (CDC), homogeneous charge compression ignition (HCCI), and reactivity controlled compression ignition (RCCI). Afterward, the influence of the gas velocity and the pressure difference perpendicular to the walls were included in the SCC model to consider their contributions to the heat fluxes near the chamber walls. It is found that the heat fluxes predicted by the SCC model are in better agreement with the experimental data, especially in the CDC mode under different swirl ratios and loads. The peak of the heat flux predicted by the SCC model shows superiority to that of the previous steady heat transfer models and the unsteady heat transfer model.